ON THE ESSENCE AND EFFICIENCY OF PROGRAMME BUDGETING - Andrei PETROIA (Eastern European Journal of Regional Studies)
The program budgeting applies to cases where expenditure is classified in the budget by objectives (outcomes and outputs) rather than solely by economic categories (i.e., inputs such as salaries) and organizational category. Performance budgeting (or performance-informed budgeting) refers to a wider set of initiatives intended to strengthen the links between the funds provided and the results achieved through ensuring performance information is used in resource allocation decision making. Program and performance budgeting reforms should, therefore, provide information in a way that informs choices about spending alternatives and should improve transparency and accountability of government. There is no “best practice” approach, more “best fit” and the unique context of each country needs to be considered. It could be noted that some key public finance specialists recommend getting the “basics” right first as a priority. At the end of given research, there is introduced an experience of programme budgeting in Hungary, which has already have good results of its use.